Analysis of the Feasibility of the Restructuring Plan: A Case Study of Poland - Gawron, Krzysztof (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: The aim of the study is to assess the possibility of using the cost-benefit analysis (CBA) method as a practical tool for analysing the feasibility of restructuring plans prepared in accordance with Polish restructuring law regulations.Research Design & Methods: Qualitative methods, i.e. analysis of documents and review of literature and legal acts, as well as quantitative methods, i.e. cost-benefit analysis, were used for the analyses. The article uses data obtained as part of pilot scientific research of court files of restructuring cases conducted in the District Court for the capital city of Warsaw in 2016–2021.Findings: The article presents the principles of feasibility analysis using this method and then presents its advantages and limitations in the case of assessing restructuring plans. The main identified limitation is the lack of the need to present cash flow forecasts in the plan in accordance with the regulations of the Polish restructuring law. Information on projected revenues and expenses is necessary to assess the effectiveness and financial sustainability of the project.Implications / Recommendations: The cost-benefit analysis method is a useful practical tool for clear assessment of restructuring plans submitted during restructuring proceedings and it allows us to objectively assess and make a rational decision whether a given project is worth implementing and whether it requires public funding.Contribution: The research expands knowledge about methods of analysing restructuring plans.